1993
DOI: 10.1177/089033449300900422
|View full text |Cite
|
Sign up to set email alerts
|

Support Network Utilization by Breastfeeding Mothers

Abstract: The Utilization of Support Network Questionnaire (USNQ) was developed to determine how mothers utilize their network for successful breastfeeding. Sixty breastfeeding mothers completed the USNQ. Lactation consultants were the most utilized resources for providing expert information and answering questions. Husbands, friends, or family were important resources for closest personal facets of breastfeeding, including encouraging confidence. At two weeks postpartum, breastfeeding mothers had larger total support s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 5 publications
1
15
0
1
Order By: Relevance
“…In a study of 200 women, Giugliani et al (1994) concluded that, regardless of maternal age, education level, ethnicity, and marital status, women who indicated that their partners preferred breastfeeding were significantly more likely to initiate breastfeeding when compared with women whose partners were ambivalent or preferred bottle-feeding (OR = 32.8, 95% CI = 6.7-159.5). In studies conducted after the birth of the infant, the partner's breastfeeding attitude still remained the most influential factor in the women's decision to initiate breastfeeding; partners were more important than physicians, lactation consultants, or nurses (Buckner & Matsubara, 1993;Libbus & Kolostov, 1994). Auspiciously, Giugliani et al, in a study of 181 U.S. fathers, found that although male partners generally had poor knowledge of breastfeeding, fathers who received breastfeeding information from professionals were significantly more likely to promote breastfeeding with their partners.…”
Section: Sources Of Supportmentioning
confidence: 99%
“…In a study of 200 women, Giugliani et al (1994) concluded that, regardless of maternal age, education level, ethnicity, and marital status, women who indicated that their partners preferred breastfeeding were significantly more likely to initiate breastfeeding when compared with women whose partners were ambivalent or preferred bottle-feeding (OR = 32.8, 95% CI = 6.7-159.5). In studies conducted after the birth of the infant, the partner's breastfeeding attitude still remained the most influential factor in the women's decision to initiate breastfeeding; partners were more important than physicians, lactation consultants, or nurses (Buckner & Matsubara, 1993;Libbus & Kolostov, 1994). Auspiciously, Giugliani et al, in a study of 181 U.S. fathers, found that although male partners generally had poor knowledge of breastfeeding, fathers who received breastfeeding information from professionals were significantly more likely to promote breastfeeding with their partners.…”
Section: Sources Of Supportmentioning
confidence: 99%
“…Breast-feeding mothers typically have larger support scores on self-report measures, 45 and expectant mothers whose partners were with them during infant care interventions were significantly more likely to initiate breastfeeding for their newborn. While the diversity and newness of the Latino community in Cincinnati limit the opportunities for community building among Latinas, our data suggest this could be an important area of intervention.…”
Section: Next Stepsmentioning
confidence: 99%
“…In addition, information was collected related to ethnicity, level of education, and whether the woman had a close relative who had breastfed. The decision to include information about ethnicity, education, and relatives was based on earlier research that indicates these variables influence breastfeeding duration (Aikin, 1999;Buckner & Matsubara, 1993;Forste, Weiss, & Lippincott, 2001;Ryan et al, 2002).…”
Section: Instrumentmentioning
confidence: 99%